A Methodology To Determine Product Maintainability Based On Assembly Criteria - A Case Study Of Rear Matorcycle Brake Assembly. - Abdullah, Ahmad Baharuddin; Yusoff, M. S.; Hasim, M.H; Shuib, S (2006)
This paper presented a methodology to determine a maintainability index based on assembly criteria. Typically time is the major parameter or indicator being used measuring the maintainability, but less works are focus on details components assembly and assembly criteria.